Genetic Alterations in Presumptive Precursor Lesions of Breast Carcinomas - Michaela Aubele; Martin Werner; Heinz Höfler (Analytical Cellular Pathology)
The hypothetical multistep model of breast carcinogenesis suggests a transition from normal epithelium to invasive carcinoma via intraductal hyperplasia (without and with atypia) and in situcarcinoma. These presumptive precursor lesions are currently defined by their histological features, and their prognosis is imprecisely estimated from indirect epidemiological evidence. Cytogenetic and molecular‐genetic analysis of these lesions give evidence for an accumulation of various genetic alterations during breast tumorigenesis. Using immuno‐histochemistry overexpression of the c‐erbB‐2 oncogene was found in ductal carcinoma in situ(DCIS), but not in atypical intraductal hyperplasia (AIDH) and intraductal hyperplasia (IDH). An expression of mutant p53 tumor suppressor gene as well as expression of cyclin D1 was identified in DCIS. In IDH lesions loss of heterozygosity (LOH) at various loci could be identified, and comparative genomic hybridization (CGH) and fluorescence in situhybridization (FISH) studies delivered evidence for DNA amplification on chromosomal region 20q13 in the early stage of IDH. However, little is currently known about genetic alterations in those premalignant lesions, and the chronology of genetic alterations and histopathological changes during carcinogenesis is mainly undiscovered. Figure 1 can be viewed in colour on http://www.esacp.org/acp/2002/24‐23/aubele.htm